Ag-In-Zn-S quantum dots for hybrid organic-inorganic solar cells - Kim E. (2017)
© 2016 The Japan Society of Applied Physics. Quantum dots of (AgIn) x Zn 2(1-x) S 2 (x = 0.6, 0.8, and 1.0) capped by oleylamine were prepared and applied for hybrid organic-inorganic solar cells consisting of glass-indium-tin-oxide/ZnO/(AgIn) x Zn 2(1-x) S 2 /poly(3-hexylthiophene)/MoO 3 /Ag. The short-circuit current density (Jsc) and opencircuit voltage (Voc) of the hybrid solar cells were measured, and we found a low power conversion efficiency (PCE) below 0.1-. From the incident photon-to-current efficiency (IPCE) profiles of the hybrid devices, there is no marked photocurrent generation from 350 to 700 nm, which is ascribed to the absorption region of (AgIn) x Zn 2(1-x) S 2 . To improve the photovoltaic performance, ligand substitution from oleylamine to pyridine was performed. The PCE of the hybrid cell using the pyridine-capped (AgIn) x Zn 2(1-x) S 2 was improved twofold in terms of both Jsc and Voc as compared with that of the oleylamine-capped one. In particular, from the IPCE measurements, a remarkable (more than doubled) enhancement of photocurrent generation from 400 to 450nm was observed with the pyridine-substituted nanoparticles.